The genesis of schizophrenic experience: between constitution and repetition - Sganga, Michela (Scenari, 2021)
The present contribution is aimed at investigating schizophrenic autism as the basal core of schizophrenia, both in relation to the typical schizophrenic alienation and to the structures of the constitution of experience. As Blankenburg’s research on the loss of natural evidence has pointed out, what is peculiar about schizophrenic experience is a kind of innaturality that phenomenology, by shifting the attention back to the pre-reflexive dimension, can contribute to comprehend in its specific motivations. If so, then autism, as shown by Arnaldo Ballerini’s studies, can be seen not only as a transversal trait of schizophrenias but also as the own form assumed by every schizophrenia for the individual patient. On the basis of such an understanding of this phenomenon, it becomes possible to undertake a genetic investigation – started by Binswanger in his last works – of the temporal style occurring in schizophrenic experience: in this article, in particular, we will offer an original interpretation of this last aspect by making specific reference to the images of module and rhythm.